Determinants of loyalty toward Booking.com brand - Raquel da Silva e Cruz; Alzira Maria da Ascens\~ao Marques (The International Journal of Management Science and Information Technology (IJMSIT), 2014)
Relations 'customer - supplier' are increasingly more valuable and less consistent, especially in the online context. In this sense, the supplier seeks to make a website visitor into a satisfied customer and a satisfied customer into a loyal customer as a condition to become more competitive. Understanding what determines the loyalty of an online customer and the role of satisfaction and trust in this relationship is the main purpose of this research. So, based on information gathered through a questionnaire in a sample of 104 customers of the Booking.com portal, we performed a quantitative study, transversal and exploratory, in order to study the relationship between the variables: website characteristics, personality of online consumers, e-satisfaction, e-trust and brand loyalty to Booking.com. The results showed that the personality of Booking.com customers and e-satisfaction are able to explain customers' loyalty toward Booking.com brand.
Keywords: 650; e-loyalty; e-commerce; e-satisfaction; e-trust; personality of the consumer